Synthesis and electrochemical characterization of PDDA-mixed polyvinyl alcohol ion exchange membrane for salinity gradient power generation - Curampez, Reynold E.; de Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Global warming and air pollution are linked to the widespread consumption of fossil fuels. In recent years, reverse electrodialysis has been identified as an alternative sustainable, renewable and non-polluting energy resources that has a potential for mass use. In this study, anon exchange membranes for reverse electrodialysis application were synthesized by combining PVA and PDDA at varying mass ratios. The membranes produced had an average thickness of 60 microns. SEM micrography of membranes were tested for electrical resistance, permselectivity, ion exchange capacity, water uptake and power generation using reverse electrodialysis. The highest power density obtained was 1.25 W/m2. Permselectivity, ion exchange capacity and swelling degree increased with higher PDDA mass ratio while an opposite trend was observed for electrical resistance.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Ion-permeable membranes; Renewable energy sources; Electrodialysis